CAN CRYPTOCURRENCY BE A HEDGE DURING CRISIS? A SYSTEMIC RISK POINT OF VIEW - Pangestuti, Rinda Siaga (Universitas Nusa Cendana, 2025)
This study investigates the hedging possibilities of cryptocurrency assets using a systemic risk estimation approach during the COVID-19 crisis period. Using a quantitative research approach, the research uses S&P 500 index price data and cryptocurrency assets. The systemic risk is calculated by using the vine copula ΔCoVaR method and the APARCH-DCC approach on the portfolio of cryptocurrency assets calculated for both individual cryptocurrency assets and GMV portfolios to capture the non-linear and dynamic relationship between cryptocurrencies and other financial assets and to estimate the impact of risk induced by the asset portfolio on the index under extreme market conditions. As a result, in the short term, especially during the Covid-19 crisis, BTC is considered the first